Metabolomics-based profiles predictive of low bone mass in menopausal women - Takeshi Miyamoto; Akiyoshi Hirayama; Yuiko Sato; Tami Koboyashi; Eri Katsuyama; Hiroya Kanagawa; Atsuhiro Fujie; Mayu Morita; Ryuichi Watanabe; Toshimi Tando; Kana Miyamoto; Takashi Tsuji; et al. (Bone Reports, 2018)
Osteoporosis is a skeletal disorder characterized by compromised bone strength and increased risk of fracture. Low bone mass and/or pre-existing bone fragility fractures serve as diagnostic criteria in deciding when to start medication for osteoporosis. Although osteoporosis is a metabolic disorder, metabolic markers to predict reduced bone mass are unknown. Here, we show serum metabolomics profiles of women grouped as pre-menopausal with normal bone mineral density (BMD) (normal estrogen and normal BMD; NN), post-menopausal with normal BMD (low estrogen and normal BMD; LN) or post-menopausal with low BMD (low estrogen and low BMD; LL) using comprehensive metabolomics analysis. To do so, we enrolled healthy volunteer and osteoporosis patient female subjects, surveyed them with a questionnaire, measured their BMD, and then undertook a comprehensive metabolomics analysis of sera of the three groups named above. We identified 24 metabolites whose levels differed significantly between NN/LN and NN/LL groups, as well as 18 or 10 metabolites whose levels differed significantly between NN/LN and LN/LL, or LN/LL and NN/LN groups, respectively. Our data shows metabolomics changes represent useful markers to predict estrogen deficiency and/or bone loss. Keywords: Metabolomics, Metabolite, Women, Estradiol, Estrogen, Menopause, Bone mineral density